Effect of potato (Solanum tuberosum) meal on broiler production (Bangladesh Journal of Animal Science, 2014)
The study was conducted to find out the performance of broiler birds fed different levels of potato meal (PM). The levels of potato meal in the different treatment rations were control 0, 5, 10, and 15 g/kg, respectively. Dietary levels of PM did not affect live weight at 7, 21, 28, 35 and 42 days of age. However, live weight of broiler differed significantly (p